2015
DOI: 10.1007/s12020-015-0826-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of pathologically versus clinically negative lymph nodes is associated with reduced use of radioactive iodine post-thyroidectomy for low-risk papillary thyroid cancer

Abstract: Cervical lymph node metastases are common in papillary thyroid cancer (PTC). Clinically negative lymph nodes confer uncertainty about true lymph node status, potentially prompting empiric postoperative radioactive iodine (RAI) administration even in low-risk patients. We examined the association of clinically (cN0) versus pathologically negative (pN0) lymph nodes with utilization of RAI for low-risk PTC. Using the National Cancer Database 1998–2011, adults with PTC who underwent total thyroidectomy for Stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In patients with cN0 disease, we observed that higher lymph node yields were associated with a higher likelihood of identifying 1 positive lymph node. Thus, there may be a diagnostic benefit to removing more lymph nodes in facilitating accurate pathologic staging of the neck, which subsequently may have an impact on decisions regarding adjuvant therapy . Another possibility is that removing more lymph nodes serves a therapeutic role in treating occult lymph node disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with cN0 disease, we observed that higher lymph node yields were associated with a higher likelihood of identifying 1 positive lymph node. Thus, there may be a diagnostic benefit to removing more lymph nodes in facilitating accurate pathologic staging of the neck, which subsequently may have an impact on decisions regarding adjuvant therapy . Another possibility is that removing more lymph nodes serves a therapeutic role in treating occult lymph node disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may be a diagnostic benefit to removing more lymph nodes in facilitating accurate pathologic staging of the neck, which subsequently may have an impact on decisions regarding adjuvant therapy. 37 Another possibility is that removing more lymph nodes serves a therapeutic role in treating occult lymph node disease. Finally, higher lymph node yields may more broadly reflect better care provided by a surgeon or hospital, resulting in improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…MEE includes extension to sternothyroid muscle or perithyroid soft tissue and is classified as T3 and consequently, upstages T1 and T2 differentiated thyroid cancer (DTC) patients aged older than 45 years to stage III disease (Edge & Carducci 2009). Upstaging appears to affect the decisions involving the extent of resection and radioactive iodine therapy (RAI) (Haugen et al 2016, Ruel et al 2016. Impact of MEE on the survival is a controversial topic and was investigated by different single institution studies mostly from Asia (Ito et al 2006a,b, Hotomi et al 2012, Shin et al 2013.…”
Section: :5mentioning
confidence: 99%
“…Unsatisfactory neck dissection might reduce the diagnostic bene t by removing insu cient lymph nodes, detecting a low incidence of extracapsular spread and facilitating an inaccurate N staging, which subsequently might interfere the decisions on adjuvant treatment. [26,33] Several studies had stated that extensive neck dissection could certainly reduce the regional recurrence, which might be compensated by PORT among patients who underwent unsatisfactory neck dissection or with advanced N stage. [34][35][36] The unmarried status was found correlated with decreased CSS, including windowed, single, separated and divorced.…”
Section: Discussionmentioning
confidence: 99%